How to Create and Use State-Level Policy Data Sets in Education Research. (September 2019) - Kelchen, Robert; Rosinger, Kelly Ochs; Ortagus, Justin C.
As state governments seek to improve the performance of institutions of K–12 and higher education, they often adopt educational policies that have similar names but different characteristics across states and with variations over time within states. Yet quantitative analyses generally examine the absence or presence of an educational policy instead of diving into details such as the dosage or percentage of funding tied to a policy or the specific groups being targeted by the implementation of the policy. The aim of this article is to provide guidance for education policy researchers in constructing and analyzing detailed data that can inform the design of state-level policies, using state performance-based funding policies in public higher education as an example. We also show how to conduct difference-in-differences analyses with continuous treatment variables in order to take advantage of more-nuanced data and better understand the context in which policies are effective (or ineffective).